The state of smokeless tobacco cessation in a context lacking cessation services: Evidence from Ethiopia - Mamusha A. Hussen; Edao S. Etu (Tobacco Induced Diseases, 2019)
Introduction Cessation attempts for smokeless tobacco (SLT) have been studied in the countries that provide comprehensive cessation services, but there is no evidence about SLT cessation in Ethiopia, where there are no comprehensive tobacco cessation services. The objective of this study was to determine cessation attempts and related factors among daily SLT users.